Trauma Nurses’ Mental Health: A Contemporary Review of Vicarious Trauma, Burnout, and Resilience (2020–2025) - Yuni Suharnida Lubis (Journal of Innovative and Creativity, 2025)
PurposeThis study aims to examine the interrelationship between vicarious trauma, burnout, and resilience in trauma nurses, as well as to identify resilience strategies that support their mental health and professional sustainability. Nurses working in trauma and emergency care settings are frequently exposed to human suffering, critical injuries, and death, which can cause significant psychological strain. Understanding these relationships is essential to develop evidence-based interventions that promote mental health and resilience among trauma nurses. Materials and Methods.This study employed a systematic literature review approach with a descriptive-analytical design. Data were collected from Scopus, PubMed, ScienceDirect, and CINAHL databases for the period 2020–2025. A total of 382 articles were identified using the keywords “trauma nurse,” “vicarious trauma,” “burnout,” “resilience,” and “mental health.” After applying inclusion and exclusion criteria, 25 eligible studies were analyzed following the PRISMA 2020 protocol. Data extraction focused on study design, sample characteristics, and relationships among the main variables. Results.The synthesis shows that vicarious trauma significantly increases the risk of burnout among trauma nurses. Burnout, in turn, has a strong negative impact on mental health outcomes. Resilience plays a crucial mediating role, reducing the negative influence of both vicarious trauma and burnout. Institutional support, peer debriefing, and mindfulness-based resilience training are identified as effective interventions for enhancing psychological well-being. Conclusions.Vicarious trauma and burnout remain major psychological risks in trauma nursing practice. However, resilience serves as a vital protective factor that improves adaptability and emotional recovery. Strengthening resilience through structured mental health programs and trauma-informed leadership is essential to ensure sustainable well-being and performance among trauma nurses.